2016
DOI: 10.1007/s11523-016-0458-1
|View full text |Cite
|
Sign up to set email alerts
|

Regorafenib in the Real-Life Clinical Practice: Data from the Czech Registry

Abstract: Regorafenib is a well-established treatment for pretreated patients with mCRC, however real-life data are scarce. Our results demonstrated slightly better efficacy of regorafenib and better safety profile in patients with mCRC compared to the randomised trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 15 publications
4
13
0
Order By: Relevance
“…Median PFS was 3.9 months (95% CI 3.3 to 4.5 months) and median OS was 7.6 month (95% CI 4.2 to 11.1 months). Interestingly, in a comparative European study, survival data was also higher than that found in the original CORRECT trial [4]: in that 2017 Czech registry study, Kopeckova K. et al [12] also report PFS of 3.5 months and median OS of 9.3 months in 148 patients; and these results are similar to our findings (PFS 2.9 months, Table 3, Figure 1B). Even if our data is retrospective, it remains consistent with other regorafenib studies [13].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Median PFS was 3.9 months (95% CI 3.3 to 4.5 months) and median OS was 7.6 month (95% CI 4.2 to 11.1 months). Interestingly, in a comparative European study, survival data was also higher than that found in the original CORRECT trial [4]: in that 2017 Czech registry study, Kopeckova K. et al [12] also report PFS of 3.5 months and median OS of 9.3 months in 148 patients; and these results are similar to our findings (PFS 2.9 months, Table 3, Figure 1B). Even if our data is retrospective, it remains consistent with other regorafenib studies [13].…”
Section: Discussionsupporting
confidence: 90%
“…Retrospective data on regorafenib real-life use seeks to address therapy response and cost effectiveness, but little data is available [10][11][12]. In this single center registry study, we analyzed treatment response after regorafenib administration in different therapy lines and compared clinical outcomes with those achieved in previous studies.…”
mentioning
confidence: 99%
“…In fact, both urinary neopterin and CRP correlated with baseline CEA concentration, a parameter that, despite some limitations, approximates the tumor mass. The findings of the present study may have obvious implications for the management of patients presenting for second or higher line of therapy although the algorithm of the treatment of metastatic colorectal carcinoma has changed, and with anti-EGFR therapy moving to the front-line [22] other treatments, including combination of chemotherapy with aflibercept or bevacizumab, regorafenib or different chemotherapy regimens are being used and the search for new active agents continues [28][29][30]. In this population of, sometimes heavily, pretreated patients, the potential benefit of the therapy should be carefully weighted against its complications.…”
Section: Discussionmentioning
confidence: 93%
“…Thirty-two retrieved articles were clinical trials or series. After exclusion of 12 reports describing phase I, II and III trials and eight case reports or series with few patients, 12 retrospective series remained to be included in the current analysis (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26). These reports were published between 2015 and 2017 and described a total of 702 patients (Table I).…”
Section: Resultsmentioning
confidence: 99%
“…The preponderance of reports came from Asian populations, thus making the relevance of results for other populations debatable. Nevertheless, two out of the three most extensive series (22,25) accounting for more than half of the total patients analyzed were from Europe.…”
Section: Discussionmentioning
confidence: 99%